The Role of Human Resource Education: An Essential Driver in Advancing Economic Progress through Entrepreneurship Exploration - Hanif, Muh; Ukar, Kurweni; Permana, Budi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Education is considered the primary foundation for economic development. Through education, individuals acquire the skills and knowledge necessary to effectively participate in the global economy. Entrepreneurship plays a crucial role in driving the economy through job creation, enhanced competition, and innovation. Entrepreneurship education can enhance individuals' abilities to start and manage their own businesses. This research aims to explore how human resource education can serve as an essential driver in advancing economic progress through entrepreneurship exploration. This study is a literature review using a qualitative approach with descriptive analysis. Data were gathered from articles published on Google Scholar between 2013 and 2024 through keywords HR Education, Economic Progress, Entrepreneurship. The study results indicate that human resource education plays a crucial role in driving a country's economy through harnessing entrepreneurial potential. Education is not only about transferring knowledge but also shaping character, skills, and attitudes that support innovation and competitiveness. In an increasingly interconnected global context, education also serves as a bridge between local innovation and the global market, creating an inclusive and sustainable environment for economic growth